The effects of board composition and board size on the informativeness of annual accounting earnings - Ahmed, K.; Hossain, Mahmud; Adams, M. (Blackwell Publishing, 2006)
This study extends earlier research on corporate governance by examining whether the information-usefulness of annual accounting earnings varies with the fraction of outside directors serving on the board and board size. Using panel data from New Zealand (NZ) firms for the financial years 1991-97, we find that earnings informativeness is negatively related to board size but is not related to the fraction of outside directors serving on the board. Our results are robust to controlling for various firm-specific factors that are known to be associated with earnings informativeness.